323 NEUROTOXICITY OF ETHANOL AND HYPOXIA IN RAT PRIMARY NEOCORTICAL CELL CULTURES. (10th December 2015) - Lee, B. H.; Genetta, T.; Rogido, M.; Wen, T. C.; Sola, A.
Abstract : Background: Fetal alcohol syndrome is a leading cause of preventable neurodevelopmental disability. Hypoxia is another common fetoneonatal insult. However, there has been little investigation regarding the neurotoxic effects of these two common events in combination, as likely occurs in clinical situations. This abstract presents our preliminary findings as we establish an in vitro model to address this question. Objectives: To quantitate the degree of neurocytoxicity induced by varying concentrations of ethanol and durations of hypoxia on fetal rat neurons in vitro. Methods: Fetal cortices from E18 Sprague-Dawley fetuses were used to obtain primary neocortical cell cultures using standardized protocols. Cultures were incubated in 5% CO2 at 37°C for 5-7 days prior to experimentation. Cultures were subjected to ethanol concentrations ranging from 0%-0.50% for either 24 or 48 hours. Additional cultures were subjected to < 1% FiO2 for between 0-60 minutes in a hypoxia chamber flushed with 95% N2 and 5% CO2. LDH supernatant levels were used to determine percent cell death after the various culture conditions. All cultures were subsequently incubated with 1% Triton-X to obtain high controls; cultures subjected to neither ethanol nor hypoxia served as low controls. The LIVE/DEAD Viability/Cytotoxicity Kit (Molecular Probes) was used to qualitatively assess cell death by fluorescence microscopy. Results: Primary neocortical rat cell cultures incubated for 24 hours with ethanol showed 0.8% cytotoxicity with 0.01% ethanol, 1.7% with 0.05%, 1.4% with 0.1%, 5.3% with 0.25%, and 7.7% with 0.5%. After 48 hours of ethanol incubation, cytotoxicity increased to 28.3% with 0.01% ethanol, 16.8% with 0.05%, 17.3% with 0.1%, 48.3% with 0.25%, and 61.6% with 0.5%. Cytotoxicity was 14.3% after 5 minutes of hypoxia, 22.8% after 10 minutes, 30.8% after 15 minutes, and 28.2% after 30 minutes. Fluorescence microscopy with LIVE/DEAD staining confirmed cytotoxicity determinations by LDH measurements. Conclusions: There was a dose-response relationship between increasing ethanol concentration and neuronal cell death but a relative neuroprotective effect provided by 0.05%-0.1% ethanol compared to either lower or higher ethanol concentrations, a finding consistent with published reports. Hypoxia-induced neurocytotoxicity plateaued after 15 minutes of hypoxia; it is unclear whether this is due to persistence of low but effective oxygen tensions or the beginning of a multimodal effect. Studies on possible synergistic effects between ethanol and hypoxia on neurocytotoxicity and possible pharmacologic modulations of in vitro cell death are currently being performed.